Edukasi Perawatan Luka Diabetes Kepada Masyarakat Dalam Upaya Pencegahan Komplikasi - Baso Witman Adiaksa; Febri Sriyanti; Hartati Hartati; Nadirah Nadirah; Rahmat Pannyiwi (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Diabetes mellitus is a chronic disease that often leads to complications, one of which is diabetic wounds, which carry a high risk of infection and amputation if not properly cared for. Poor public knowledge and skills regarding diabetic wound care are major factors contributing to further complications. This Community Service activity aims to improve the community's knowledge, attitudes, and skills in diabetic wound care as an effort to prevent complications. Implementation methods included health education, diabetic wound care demonstrations, hands-on practice, and evaluation through pre- and post-tests. The results of the activity indicated an increase in community knowledge and skills regarding diabetic wound care and infection prevention. Education on diabetic wound care is expected to reduce the risk of complications and improve the quality of life of people with diabetes.